A discursive analysis concerning information on "ADHD" presented to parents by the National Institute of Mental Health (USA). Issue 1 (1st January 2016) - Erlandsson, Soly; Lundin, Linda; Punzi, Elisabeth
Abstract : A discourse analysis was performed based on an online document under the headline: "What is Attention Deficit Hyperactivity Disorder (ADHD, ADD)?" published by the National Institute of Mental Health (NIMH), USA. Three parts of the document were analysed: (1) The introductory part, as this sets the tone of the whole text. (2) Parts of the text that were specifically addressed to parents. (3) Etiology and pathology of "ADHD" with reference to a number of different symptoms and behaviors. Inattention and hyperactivity are presented in the document as a floating spectrum of symptoms caused by "ADHD." Other factors of importance for children's development, that is, early attachment, close relationships, previous experiences, culture, and contexts are ignored. Children who are perceived as inattentive and hyperactive are portrayed as having inherent difficulties with no reference to their emotions or efforts to communicate. The child is viewed as suffering from a lifelong disorder that might not be cured but controlled by a diagnosis and subsequent medication. Parents are advised to control their child's behavior and to strive for early diagnosis in order to receive treatment provided by experts. Those who are presented as experts rely on a biomedical model, and in the document, detailed descriptions of medication to correct the undesired behaviors are provided. The value of judgment in the assessment of different symptoms and behaviors that signifies "ADHD" is absent, rather taken-for-granted beliefs were identified throughout the document. A heterogeneous set of behaviors is solely described as a disorder and hereafter it is stressed that the same behaviors are caused by the disorder. In this manner, cause and effects of "ADHD" are intertwined through circular argumentation.